Financial Distress Analysis in Detecting Bankruptcy Levels in Manufacturing Companies - Ayu, Intan Sury; Putri, Andini Utari (International Journal of Community Service & Engagement, 2024)
The methodology used is the Altman method, the Springate method and the Zmijewski method for the 2015-2019 period. The type of data used is quantitative data. The data analysis technique used is the formula of the Altman method, the Springate method and the Zmijewski method. The results of this study show that in the 2015 and 2019 Altman method there are eight or all companies that are predicted to be in the bankrupt category. Meanwhile from 2016 to 2018 there are only six companies that are included in the bankrupt category and two other companies are categorized in the gray zone. In the Springate method from 2015 to 2019, there are eight or all companies predicted to have the potential to go bankrupt. In the zmijewski method from 2015 to 2017 there were five companies that were in the bankrupt category while in 2018 to 2019 there were only two companies that were included in the bankrupt category. In addition, based on the different results through the one-way ANOVA test, a significant value <0.05 was obtained, which means that there was a significant difference between the methods tested.